EFFECT OF GROWTH REGULATORS AND HAULMS KILLING DATES ON BIOCHEMICAL COMPONENTS OF POTATO TUBERS UNDER NILGIRI CONDITIONS - Ravichandran, G.; Natarajan, N.; Vanangamudi, K (Potato Journal, 2013)
Field trials were conducted during 2003 and 2004 to study the effect of different growth regulators on biochemical properties of tuber viz., reducing sugars, total free amino acids, sucrose, phenols and also tuber dry matter. Application of CCC resulted in lower total free amino acids and phenols in comparison with control. Reducing sugar content was higher on application of prosopis pod extract and CCC. Sucrose content of tubers also increased with CCC treatment. Delaying the haulm killing from 90 to 105 days reduced the reducing sugar accumulation in tubers.